Posthuman Encounters and Patterns of Care in Klara and the Sun (2021) or, What Ishiguro’s AI Tells Us About the Uncanny Valley - Leblond, Diane (Journal of Posthumanism, 2024)
The protagonist of Ishiguro’s Klara and the Sun (2021) seems like a perfect candidate to take us through the uncanny valley — the place conceptualised by Masahiro Mori (1970)— where the once attractive almost-but-not-quite-human suddenly repulses us. Klara is an android whose AI capabilities make her the best companion to Josie, a teenager afflicted with a potentially fatal condition. She is also a sympathetic first-person narrator and internal focaliser, until a plot twist presents her in an entirely different light. Told from the android’s viewpoint, the fable informs our experience of the uncanny valley. Mori’s model focused on appearance, but our discomfort stems from the notion that Klara might replicate human consciousness. This brings up the hypothesis of an ‘uncanny valley of the mind.’ Yet through most of the story sharing the AI’s perspective is exhilarating rather than off-putting.